Implementation of Hybrid Learning and Its Impacts at A Public Junior School in Indonesia - Fanani Riski Dwi; Nadi Suprapto; Zainul Arifin Imam Supardi (Indonesia Approach Education, 2022)
The pandemic of COVID-19 has made several change to the learning process in Indonesia. Because of the less effective online learning, the Indonesian Ministry of Education and Culture creates new policies by allowing offline learning, but with a limited system or hybrid learning. The purpose of this study was to find out how the implementation of hybrid learning in schools, where placed at a Public Junior School in Indonesia. The type of this research is a qualitative research using interview and observation techniques involving the Principal, Deputy Principal for Curriculum, English Teachers, Social Sciences Teachers, and Science Teachers. The data obtained will be analyzed with Miles and Huberman technique. This implementation has several stages, namely the preparation/planning, the implementation, and the evaluation. During this pandemic, online and hybrid learning process has had a big impact. The positive impact is to make teachers more literate towards digital technology which makes them more creative and innovative in choosing learning media platforms, and student’s skills were improve in using technology.